Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of Romania on Termination of the Agreement between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of Romania for the Promotion and Reciprocal Protection of Investments done at London on 13 July 1995 and the Extending Exchange of Notes, Bucharest, 27 and 30 March 2022. ([2022-11-30]) - Unknown
No abstract available